PERILAKU MENGAJAR GURU BIOLOGI PASCA SERTIFIKASI DI KOTA DENPASAR - Ida Bagus Ari Arjaya; Kadek Rahayu Puspadewi (Jurnal Bakti Saraswati (JBS): Media Publikasi Penelitian dan Penerapan Ipteks, 2017)
The purpose of this research is to analyze the quality: 1) the level of clarity of the method used by the teacher, 2) the teacher's enthusiasm level, 3) the interaction done by the teacher in the class, 4) the quality of setting & arrangement of the subject, 5) step of giving information, 6) assessment criteria in the classroom, 7) teacher's voice, 8) level of proximity relation between teacher and student. This research is a qualitative research using descriptive approach with purposive sampling method. So determined two schools namely SMP 3 Denpasar and SMP Saraswati 1 Denpasar which became the location of research. A total of 2 model teachers were observed using teacher teaching behavioral instruments, and interviews and as data triangulation used 2 observers and 73 students as respondents. The results showed that in 1) the clarity aspects of teaching post-certification biology teachers in Denpasar City with a total mean of = 3.90 and being in good qualification 2) the aspect of teacher's enthusiasm is in good category with total mean = 3.57, 3) The interaction aspect to develop student participation is in good category with the total mean = 3,73,4) the arrangement aspect for arranging subject of teacher lessons is in good category with mean total = 4,18,5) aspects of steps in giving information teachers are in good category with the total mean = 4.04, 6) the aspects of teacher learning and teacher's criteria are in good category with the total mean = 4.08,7) the teacher characteristic aspect is in either category with the total mean = 4.13 , 8) aspects of the teacher's sound characteristics with the students are in the medium category with the total mean = 3.29, and the need for improvement.